Multi-scale multi-physic coupled investigation on the matching and trade-off of conversion and storage of optical, thermal, electrical, and chemical energy in a hybrid system based on a novel full solar spectrum utilization strategy. (1st May 2023) - Zhou, Yi-Peng; Xu, Jia-Chen; Ma, Xin-Yue; Yang, Pei-Xin; He, Ya-Ling
Highlights: An efficient full solar spectrum utilization system with functions of generation and storage. An integrated multi-scale multi-physic theoretical model. Multi-scale optical structure optimization. Multi-scale multi-physic effects of air insulation and water layer. Match and trade-off between heat, and electrics and hydrogen storage. Abstract: In order to achieve a reasonable utilization of the full solar spectrum at low-cost, a photovoltaic/thermoelectric/electrolysis (PTE) hybrid system based on a novel full solar spectrum utilization strategy is proposed. The PTE mainly consist of a thermal collector with the spectrally selectively absorption fluid (water), a photovoltaic-thermoelectric (PV–TE) component and a water electrolysis component. Based the structure of the PTE, the full solar spectrum energy can be reasonably and efficiently allocated and utilized. For the complicated coupling physical process in PTE hybrid system, an integrated multi-scale multi-physic theoretical model is developed to optimize and investigate the PTE hybrid system. After the analyses on the multis-scale multi-physic effect of the air insulation layer between the thermal collector and the PV–TE component, it is found that removing air insulation layer leads to the less reflection loss and parasitic absorption, and more the maximum achievable photo current density and the internal heat source for TE component. Moreover, not only does the PV–TE component without the air insulation layer have higher efficiency (27.03%), but the concentration corresponding to the maximum efficiency increase to 31 from 3, which means more output power. By matching the structure and energy between components, the efficiency of the PTE hybrid system can be further improved, while the efficiency and energy storage of the PTE hybrid system can be adjusted according to the demand. Compared to single PV system, the efficiency of the PTE hybrid system has been increased by 15.38% at the concentration of 20, and this difference increases with the concentration. Moreover, the PTE hybrid system can simultaneously generate 200 W/m 2 of hydrogen energy at the concentration of 20. In summary, the PTE hybrid system not only offers better performance (generation and storage), but also better integration, providing a guiding idea for the full solar spectrum utilization. Moreover, the multi-scale multi-physic coupled model also provides precise theoretical guidance for the optimization and design.